The Mind Is a Collection : Case Studies in Eighteenth-Century Thought - Silver, Sean; Silver, Sean. (Philadelphia, Pa. : University of Pennsylvania Press, 2015)
The Mind Is a Collection approaches seventeenth- and eighteenth-century theory of the mind from a material point of view, examining the metaphors for mental activity that invoked the material activity of collection.
Frontmatter -- Contents -- Preface : Welcome To The Museum -- Introduction -- Case 1. Metaphor -- Case 2. Design -- Case 3. Digression -- Case 4. Inwardness -- Case 5. Conception -- Case 6. Dispossession -- Conclusion -- Notes -- Index -- Acknowledgments
Description based on online resource; title from PDF title page (publisher s Web site, viewed Nov. 24, 2015)
Keywords: Collectors and collecting -- History -- 17th century -- Case studies; Collectors and collecting -- History -- 18th century -- Case studies; Museums -- Curatorship -- England -- London -- History; Psychology, other